2020
DOI: 10.1039/d0bm00162g
|View full text |Cite
|
Sign up to set email alerts
|

A novel peptide targeting gastrin releasing peptide receptor for pancreatic neoplasm detection

Abstract: The designed novel peptide GB-6 with targeted GRPR-binding possesses more favorable pharmacokinetic properties and metabolic stability, as well as superior tumor-targeting ability in pancreatic cancer models, relative to BBN7–14.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…For example, the peptide BBN 7-14 (Gln-Trp-Ala-Val-Gly-His-Leu-Met-NH 2 ) composed of natural amino acids has a higher binding affinity with the CFPAC-1 cell line compared with the modified peptide GB-6 (Gln-5-Htp-β-Ala-Nva-Gln-His-NH 2 ) that consists of unnatural amino acids ( in vitro ). However, in vivo , BBN 7-14 has a reduced tumor-targeting ability compared with GB-6, which is stable against protease-mediate degradation and has a slightly lower uptake and slow metabolism ( 207 ). Currently, ACPs have been modified to improve specific cancer cell targets and enhance cancer cell elimination.…”
Section: Future Directionmentioning
confidence: 99%
“…For example, the peptide BBN 7-14 (Gln-Trp-Ala-Val-Gly-His-Leu-Met-NH 2 ) composed of natural amino acids has a higher binding affinity with the CFPAC-1 cell line compared with the modified peptide GB-6 (Gln-5-Htp-β-Ala-Nva-Gln-His-NH 2 ) that consists of unnatural amino acids ( in vitro ). However, in vivo , BBN 7-14 has a reduced tumor-targeting ability compared with GB-6, which is stable against protease-mediate degradation and has a slightly lower uptake and slow metabolism ( 207 ). Currently, ACPs have been modified to improve specific cancer cell targets and enhance cancer cell elimination.…”
Section: Future Directionmentioning
confidence: 99%
“…To validate the results from the in vivo fluorescence imaging, we evaluated the capacity of radioactive conjugates for in vivo-targeted detection of HepG2 tumor using small animal SPECT-CT imaging. First, [ 99m Tc]­Tc-HYNIC-PEG 4 -Ang II was radiolabeled with [ 99m Tc ]­NaTcO 4 as previously described. , Details of [ 99m Tc]­Tc-HYNIC-PEG 4 -Ang II are shown in Supporting Information. Radiochemical purity was >99%, with immediate specific activities >1.67 mCi/nmol after radiolabeling and a 18.7-min retention time for [ 99m Tc]­Tc-HYNIC-PEG 4 -Ang II (Figure S21).…”
Section: Resultsmentioning
confidence: 99%
“…IHC and IF staining were performed as previously described . All snap-frozen biopsies were embedded by the OCT compound before sliced into 5 μm thickness and processed for further pathological analysis.…”
Section: Methodsmentioning
confidence: 99%
“…BBN could bind specifically to GRPR, which is overexpressed in a variety of tumor tissues and is associated with tumor infiltration and growth. 33 Flores et al found that GRPR was detected in 100% of the glioma samples analyzed, especially in the 24 cases of GBM. Highly expressed GRPR was also observed in tumor endothelial cells.…”
Section: Sensitivity and Specificitymentioning
confidence: 99%
“…growth 33. Flores et al found that GRPR was detected in 100% of the glioma samples analyzed, especially in the 24 cases of GBM.…”
mentioning
confidence: 99%